Rescaling and Transforming: “Umbrella Agreements,” Planning Deals, and the Israeli Planning Regime - Sharon Eshel; Oren Yiftachel; Talia Margalit (Land, 2025)
This paper analyzes “Umbrella Agreements,” a policy tool implemented by the Israeli government across 32 municipalities over the past decade. Introduced in response to a deepening housing crisis, these agreements offered funding for local infrastructure in exchange for municipal consent to large-scale residential development on (mostly) state- managed land. We argue that umbrella agreements rescale the neoliberal mechanism of “planning deals” from the urban to the state (national) scale, expanding their logic to new contexts, and fundamentally transforming the Israeli planning regime. While prevailing theories of neoliberalism emphasize decentralization and privatization through “free market” mechanisms, the Israeli process is characterized by strong state control over land and a concentration of planning powers at the national level as a pre-condition for private housing development. Our analysis yields three main findings. First, upscaling planning deals erodes the state’s regulatory powers while increasing its interest as a direct beneficiary of the capitalist order. Second, these agreements subject market logic to greater political control. Third, this transformation has seriously undermined the democratic and professional characters of the planning system, leading to regressive social consequences.